Carrier dynamics in the wetting layer of InGaAs/GaAs quantum dots grown by using migration-enhanced epitaxy - An, Chengshou; Jang, Yudong; Lee, Donghan; Song, Jindong; Choi, Wonjun (KOREAN PHYSICAL SOC, 2013)
We have investigated the effects of carrier localization on the migration-enhancing time in a wetting layer (WL) of quantum dots (QDs) grown by using the migration-enhanced epitaxy (MEE) growth technique. The WL photoluminescence (PL) intensity of QD sample grown with a longer migration-enhancing time remained strong even at low excitation densities. The PL decay time at the WL peak was longer for the MEE-grown QD with a longer migration-enhancing time. Moreover, the decay times of MEE-grown QDs across the WL's PL band were longer at longer wavelengths. We conclude that the localization effect in the WL intensifies as the migration-enhancing time is increased.